Pelatihan Pembuatan Teh Daun Salam Herbal Untuk Kesehatan Di Banjarmasin Utara [Training on the Preparation of Herbal Bay Leaf Tea for Health in North Banjarmasin] - Melviani, Melviani; Komaliya, Risyda; Filemon, Dian DReki Fileni; Andriani, Ine; Rinjani, Lalu LElwin Tri Surya; Sagita, Ririn; Witin, Rafelita Septania Barek (Indonesia Berdaya, 2026)
Abstract. Gout is a metabolic disease caused by elevated uric acid levels in the blood (hyperuricemia), which can lead to joint pain and inflammation. The prevalence of gout continues to rise in line with high-purine diets and unhealthy lifestyles. Bay leaves (Syzygium polyanthum) are known to contain active compounds such as flavonoids, tannins, saponins, and essential oils that act as inhibitors of xanthine oxidase, the main enzyme involved in uric acid formation. Utilizing bay leaves in the form of herbal tea is an innovative preparation that can be developed as an alternative functional beverage beneficial for lowering uric acid levels. This community service program aims to provide training to empower women with the skills to make bay leaf-based tea as a herbal product beneficial for health. Based on the educational activities on the use of medicinal plants in the Alalak Utara neighborhood complex, particularly herbal bay leaf tea, there was a significant increase in residents' knowledge, from 52.7% before education to 94.8% after education, with an improvement of 42.1%. Abstrak. Asam urat merupakan penyakit metabolik akibat tingginya kadar asam urat dalam darah (hiperurisemia) yang dapat menimbulkan nyeri dan peradangan pada sendi. Prevalensi asam urat terus meningkat seiring dengan pola makan tinggi purin dan gaya hidup yang kurang sehat. Daun salam (Syzygium polyanthum) merupakan tanaman yang diketahui mengandung senyawa aktif seperti flavonoid, tanin, saponin, dan minyak atsiri yang memiliki sebagai penghambat enzim xantin oksidase, enzim utama dalam pembentukan asam urat. Pemanfaatan daun salam dalam bentuk teh herbal merupakan salah satu bentuk inovasi sediaan yang dapat dikembangkan sebagai alternatif minuman fungsional yang bermanfaat dalam menurunkan kadar asam urat. Pengabdian masyarakat ini bertujuan untuk memberikan pelatihan untuk memberdayakan ibu-ibu dengan keterampilan membuat teh berbahan dasar daun salam sebagai produk herbal yang bermanfaat untuk kesehatan. Berdasarkan kegiatan edukasi pemanfaatan tanaman obat di Komplek Kelurahan Alalak Utara, khususnya teh herbal daun salam, terjadi peningkatan pengetahuan warga yang signifikan, dari 52,7% sebelum edukasi menjadi 94,8% setelah edukasi, dengan peningkatan sebesar 42,1%.